2019
DOI: 10.3389/fmars.2019.00488
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Marine Microalga Tisochrysis lutea (T-iso) in Standard Toxicity Tests; Comparative Sensitivity With Other Test Species

Abstract: The marine flagellate Tisochrysis lutea (T-iso), with a global distribution, is one of the most common microalgae used as natural food in aquaculture. In recent years Tiso has also been increasingly used in toxicity testing, although it is not included in current international protocols such as ISO that relies on Phaeodactylum tricornutum and Skeletonema costatum as marine species, and Raphidocelis subcapitata as freshwater species. Sensitivity of Isochrysis galbana to selected model toxicants was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 86 publications
0
5
0
2
Order By: Relevance
“…This species is widely used in aquaculture because it contains a high amount of polyunsaturated fatty acids (PUFAs), notably docosahexaenoic acid (DHA). T. lutea also presents a promising nutraceutical and pharmaceutical potential [2][3][4] because of its high content in carotenoids and vitamins [5,6]. Preliminary analyses of its pigment composition by our research group have shown high amounts of fucoxanthin and unidentified carotenoids (named Car43 and Car48) of chemotaxonomic interest [7].…”
Section: Introductionmentioning
confidence: 98%
“…This species is widely used in aquaculture because it contains a high amount of polyunsaturated fatty acids (PUFAs), notably docosahexaenoic acid (DHA). T. lutea also presents a promising nutraceutical and pharmaceutical potential [2][3][4] because of its high content in carotenoids and vitamins [5,6]. Preliminary analyses of its pigment composition by our research group have shown high amounts of fucoxanthin and unidentified carotenoids (named Car43 and Car48) of chemotaxonomic interest [7].…”
Section: Introductionmentioning
confidence: 98%
“…The algal growth inhibition test was carried out according to the standard method from [49] adapted to T. lutea by [50]. The initial strain of T. lutea was obtained from the ECIMAT-Universidade de Vigo collection.…”
Section: Test Organisms and Bioassaysmentioning
confidence: 99%
“…Численность клеток -показатель, традиционно используемый для оценки действия веществ на микроводоросли [Panneerselvam et al, 2018;Tato and Beiras, 2019]. Хлоропласты -основная мишень действия токсических веществ у водорослей и высших растений, данный показатель изменяется при воздействии избытка тяжелых металлов и применяется для оценки физиологических нарушений у микроводорослей [Carfagna et al, 2013].…”
Section: Introductionunclassified